International trade in second-hand electronic goods and the resulting global rebound effect - Hanna Krings (Philipps-University Marburg, School of Business and Economics, 2015)
This paper analyzes the consequences of innovations in the electronic goods sector for global energy consumption and identifies a global rebound effect with respect to trade in second-hand electronic consumption goods. With the help of 2SLS-regressions, the positive influence of trade in second-hand electronics on the respective penetration rates in developing countries and the consequences for worldwide energy consumption are estimated.
Keywords: F14; F63; Q49; 330; second-hand trade; global rebound effect; energy consumption